Effects of various solvent in retrieving nacre layers from Modiolus philippinarum shells for potential tissue engineering applications - Che Abdullah, Che Azurahanim; Mohd Khairuddin, Nur Farahah; M. l., Mokhtar; N. S., Zahari; Che Abdullah, C. A. (Inderscience Publishers (IEL), 2024)
The primary objective of this project is to extract nacre from Modiolus philippinarum shells via a variety of techniques. There are five distinct methods for extracting the nacre layer, each of which employs a unique chemical treatment. Ethylenediaminetetraacetic acid (EDTA), hydrochloric acid (HCl), sodium hypochlorite (NaOCl), hydrogen peroxide (H2O2), and acetic acid treatment were all used in the current study. The effectiveness of each method is determined by the amount and quality of nacre produced after the sample has been subjected to those chemical treatments. The amount of nacre produced can be calculated using the percentage yield, whereas the XRF analysis revealed the elemental composition of each extraction method used to obtain the nacre layer. The NaOCl method was found to be the most effective method for reclaiming nacre, yielding 93.73%. In contrast, the EDTA-treated method contributed the highest percentage of Ca (99.01 %) with the fewest trace elements, which is important for bone tissue engineering applications.